Manganese in drinking water and cognitive abilities and behavior at 10 years of age: A prospective cohort study - Rahman, S.; Kippler, M.; Tofail, F.; Bölte, Sven; Hamadani, J.; Vahter, M. (US Department of health Human Sciences National INST of Health Science, 2017)
Background: Cross-sectional studies have indicated impaired neurodevelopment with elevated drinking water manganese concentrations (W-Mn), but potential susceptible exposure windows are unknown. Objectives: We prospectively evaluated the effects of W-Mn, from fetal life to school age, on children’s cognitive abilities and behavior. Methods: We assessed cognitive abilities and behavior in 1,265 ten-year-old children in rural Bangladesh using the Wechsler Intelligence Scale for Children (WISC-IV) and the Strengths and Difficulties Questionnaire (SDQ), respectively. Manganese in drinking water used during pregnancy and by the children at 5 y and 10 y was measured using inductively coupled plasma mass spectrometry. Results: The median W-Mn was 0.20 mg/L (range 0.001-6.6) during pregnancy and 0.34mg/L ( < 0.001-8.7) at 10 y. In multivariable-adjusted linear regression analyses, restricted to children with low arsenic (As) exposure, none of the W-Mn exposures was associated with the children’s cognitive abilities. Stratifying by gender (p for interaction in general < 0.081) showed that prenatal W-Mn (3 mg/L) was positively associated with cognitive ability measures in girls but not in boys. W-Mn at all time points was associated with an increased risk of conduct problems, particularly in boys (range 24-43% per mg/L). At the same time, the prenatal W-Mn was associated with a decreased risk of emotional problems [odds ratio (OR)=0.39 (95% CI: 0.19, 0.82)] in boys. In girls, W-Mn was mainly associated with low prosocial scores [prenatal W-Mn: OR=1.48 (95% CI: 1.06, 1.88)] . Conclusions: Elevated prenatal W-Mn exposure was positively associated with cognitive function in girls, whereas boys appeared to be unaffected. Early life W-Mn exposure appeared to adversely affect children’s behavior.